1992
DOI: 10.1152/jappl.1992.72.5.1902
|View full text |Cite
|
Sign up to set email alerts
|

Role of tumor necrosis factor in oxygen toxicity

Abstract: mRNA from lungs of mice exposed to high-dose oxygen (greater than 95%) for 3 days demonstrated increased expression of the genes for tumor necrosis factor (TNF), interleukin-1, and interleukin-6 compared with mRNA from lungs of mice exposed to room air. Daily treatment of mice exposed to high-dose oxygen with an antibody to TNF improved survival compared with mice receiving a similar dose of control immunoglobulin G. Pretreatment of mice with repetitive sublethal intraperitoneal doses of recombinant human TNF … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
39
1
2

Year Published

1995
1995
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(45 citation statements)
references
References 0 publications
3
39
1
2
Order By: Relevance
“…In the majority of these studies, the cytokine ligand is induced and is presumed to mediate its effects by binding to its unaltered receptor (14,(25)(26)(27)(28)(29)31). Interestingly, our studies of IL-13 highlight a different paradigm with 100% O 2 stimulating the expression of both the IL-4R␣ and IL-13R␣1 subunits of the IL-13R without altering the expression of IL-13.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…In the majority of these studies, the cytokine ligand is induced and is presumed to mediate its effects by binding to its unaltered receptor (14,(25)(26)(27)(28)(29)31). Interestingly, our studies of IL-13 highlight a different paradigm with 100% O 2 stimulating the expression of both the IL-4R␣ and IL-13R␣1 subunits of the IL-13R without altering the expression of IL-13.…”
Section: Discussionmentioning
confidence: 92%
“…A variety of lines of evidence suggests that the consequences of hyperoxia are mediated and regulated, at least in part, by the ability of 100% O 2 to induce a variety of cytokine-receptor pathways (14,(25)(26)(27)(28)(29)(30)(31). In the majority of these studies, the cytokine ligand is induced and is presumed to mediate its effects by binding to its unaltered receptor (14,(25)(26)(27)(28)(29)31).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Yang et al [58] also demonstrated the inhibition of TNF- production in a rat model of intestinal injury treated with HBOT. However, significant increases in the expression of IL-6, IL-1 and TNF- have been also reported [1,25,26,41,49].…”
Section: Discussionmentioning
confidence: 97%
“…The precise role of TNF-a in the development of hyperoxic lung damage has not yet been established. In most previous studies, exogenous TNF-a was used to explore its effects on the development of pulmonary oxygen toxicity [11][12][13][14]. We studied the effect of a single exposure to HBO on the endogenous secretion of TNF-a by blood monocytes, by macrophages from the lungs (as the main target of the oxidative insult) and by macrophages of the spleen (as a major immunoregulatory organ).…”
Section: Introductionmentioning
confidence: 99%